2010
DOI: 10.3899/jrheum.091276
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cerebral Blood Flow and Volume in Systemic Lupus Measured by Dynamic Susceptibility Contrast Magnetic Resonance Imaging

Abstract: Objective Several studies have examined abnormalities in cerebral blood flow (CBF) in patients with systemic lupus erythematosus (SLE). However, the majority of these studies have reported CBF relative to a region assumed to be normal in the brain. The purpose of the present study was to examine absolute differences in both regional CBF and cerebral blood volume (CBV) between SLE patients and healthy control subjects. Methods CBF and CBV were measured with dynamic susceptibility contrast (DSC) magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
6
29
0
Order By: Relevance
“…The two groups were similar in all demographic variables (Table 1). More extensive clinical data and findings on this cohort can be found in Table 2 and in a previous report (11). …”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…The two groups were similar in all demographic variables (Table 1). More extensive clinical data and findings on this cohort can be found in Table 2 and in a previous report (11). …”
Section: Methodsmentioning
confidence: 76%
“…The vast majority of the latter studies measured relative CBF with single photon emission computed tomography (SPECT) and found that CBF was lower in focal or broad regions of the brain with respect to a region presumed to be normal within the SLE subjects (410). However, it has recently been demonstrated using dynamic susceptibility contrast MRI (DSC-MRI) that both CBF and cerebral blood volume (CBV) may be higher in normal appearing brain tissue in SLE patients than healthy controls (11). Elevated CBF has also been observed in other neurological disorders, including epilepsy (12), stroke (13), transient ischemic attack (14), fibromyalgia (15), metabolic brain disease (16), and migraine (17).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic susceptibility contrast MRI was performed in 89 (92%) participants (64 patients, 25 controls) to assess brain perfusion (24). Brain lesions were classified as old or recent cerebral infarcts and small focal periventricular or deep white abnormalities using standard criteria (3,4,10).…”
Section: Methodsmentioning
confidence: 99%
“…SLEDAI is a reliable and valid instrument for measuring the clinical state in patients with SLE 37. In this study, significant negative Pearson correlations were found between SLEDAI, MCA PI, PCA PI, and some cognitive function tests such as short-term memory, drawing, and fluency.…”
Section: Discussionmentioning
confidence: 57%